1995
DOI: 10.1007/bf01410617
|View full text |Cite
|
Sign up to set email alerts
|

The C-reactive protein for detection of early infections after lumbar microdiscectomy

Abstract: The tendency for short hospitalization after lumbar microdiscectomy implies the need for early confirmation or disapproval of serious postoperative infections such as spondylodiscitis or deep wound infections. The C-reactive protein (CRP) is a well-known screening parameter for monitoring postoperative infectious complications in other fields. Our objective was to establish the diagnostic significance of CRP-in comparison with ESR and WBC-for monitoring infectious complications after lumbar microdiscectomy. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 25 publications
2
47
1
3
Order By: Relevance
“…CRP response in human diseases Larsson et al, (1992) performed a prospective study focused on CRP levels in 193 patients undergoing 4 types of uncomplicated elective orthopedic procedures and concluded that a normalized CRP response that follows a typical biphasic response indicate an uneventful recovery. Meyer et al (1995), proposed using CRP as a simple, reliable, and inexpensive screening test in detection of early infections after lumbar microdiscectomy. CRP levels are increased in patients with rheumatoid arthritis, juvenile idiopathic arthritis, ankylosing spondylitis and psoriatic arthritis, giant cell arthritis and rheumatic polymyalgia (Rosa Neto and Carvalho, 2009).…”
Section: Acute Phase Proteins In Human Medicinementioning
confidence: 99%
“…CRP response in human diseases Larsson et al, (1992) performed a prospective study focused on CRP levels in 193 patients undergoing 4 types of uncomplicated elective orthopedic procedures and concluded that a normalized CRP response that follows a typical biphasic response indicate an uneventful recovery. Meyer et al (1995), proposed using CRP as a simple, reliable, and inexpensive screening test in detection of early infections after lumbar microdiscectomy. CRP levels are increased in patients with rheumatoid arthritis, juvenile idiopathic arthritis, ankylosing spondylitis and psoriatic arthritis, giant cell arthritis and rheumatic polymyalgia (Rosa Neto and Carvalho, 2009).…”
Section: Acute Phase Proteins In Human Medicinementioning
confidence: 99%
“…Das C-reaktive Protein (CRP) zeigt dagegen eine Sensitivität von 64-100% und eine Spezifität von 62-95,8% [5,18]. Postoperativ muss natürlich der Verlauf des CRP, der seinen Gipfel am 2.-3.…”
Section: Diagnostikunclassified
“…Tag hat und innerhalb von 14 Tagen auf den Normalwert zurückkehrt, berücksichtigt werden [5]. Die weit verbreitete Messung der Blutsenkungsgeschwindigkeit (BSG) hat eine Sensitivität von 78,1-82% und eine Spezifität von 38,1-62% [5,18]. Auch hier ist postoperativ ein Gipfel am 4.…”
Section: Diagnostikunclassified
“…The incisionis usually unremarkable, and in fact, less than 10% ofsurgical incisions show signs of purulent infection with erythema, drainage, or dehiscence [7] . A rise in CRP values after the aforementioned timeframe correlates highly with the presence of an infection [9] . 3 cases would be reported here who developed post operative infection more than a year after surgery, had atypical organism but with floridinfection, had 1 and ½ years continuing sinus tract discharge after minimally invasive discectomy without biochemical marker changes or systemic signs and symptoms.…”
Section: Introductionmentioning
confidence: 98%